N-acetylcysteine inhibits in vivo oxidation of native low-density lipoprotein - Cui, Yuqi (Sci Rep, 2015)
Low-density lipoprotein (LDL) is non-atherogenic, while oxidized LDL (ox-LDL) is critical to atherosclerosis. N-acetylcysteine (NAC) has anti-atherosclerotic effect with largely unknown mechanisms. The present study aimed to determine if NAC could attenuate in vivo LDL oxidation and inhibit atherosclerosis. A single dose of human native LDL was injected intravenously into male C57BL/6 mice with and without NAC treatment. Serum human ox-LDL was detected 30 min after injection, reached the peak in 3 hours, and became undetectable in 12 hours. NAC treatment significantly reduced serum ox-LDL level without detectable serum ox-LDL 6 hours after LDL injection. No difference in ox-LDL clearance was observed in NAC-treated animals. NAC treatment also significantly decreased serum ox-LDL level in patients with coronary artery diseases and hyperlipidemia without effect on LDL level. Intracellular and extracellular reactive oxidative species (ROS) production was significantly increased in the animals treated with native LDL, or ox-LDL and in hyperlipidemic LDL receptor knockout (LDLR(−/−)) mice that was effectively prevented with NAC treatment. NAC also significantly reduced atherosclerotic plaque formation in hyperlipidemic LDLR(−/−) mice. NAC attenuated in vivo oxidation of native LDL and ROS formation from ox-LDL associated with decreased atherosclerotic plaque formation in hyperlipidemia.